Emerg. house 4all: A sensitive approach informed by new digital tools - Paio, A.; Rato, V.; Reis, J.; Santos, F.; Lopes, P. F. (5th European Conference on African Studies. African Dynamics in a Multipolar World, 2013)
The paper presents the progress of a multidisciplinary team who is collectively working on an integrated design tool to generate humanized urban and self-built tailored incremental housing. The ongoing project called “Emerg.cities4all” goal is to develop a system that could use the revealed cultural, social and spatial dynamics involved in the genesis of informal settlements (favelas, musseques and caniços) to autonomously generate adequate housing designs while simultaneously generating all the information needed to direct fabrication. This research explores grammar-based design and digital fabrication systems to provide modular, adaptable and affordable housing. Emerg.cities4all research project suggests that computing and fabrication algorithms are paving the way to achieve new design paradigms for low-income populations.